Meconium periorchitis: An unusual cause of newborn scrotal mass (Medical Journal of Indonesia, 2009)
A case of meconium periorchitis in a 2-month-old boy is reported. The patient was delivered normally, only a scrotal mass was noted which became harder in weeks. Clinical and intrauterine ultrasonographic findings were suggestive of a neoplasm and orchidectomy was performed. Microscopic examination revealed separate nodules of myxoid stroma with varying amounts of calcifi cation separated by fibrous septa. The unexpected diagnosis of meconium periorchitis was confirmed. This condition is due to inflammatory reaction from the meconium within the scrotal sac and resulted from an intrauterine perforation of the gastrointestinal tract. Since solid benign or malignant paratesticular masses cannot be differentiated by ultrasonography, tissue biopsy or fresh frozen tissue examination is required for diagnosis. (Med J Indones 2009; 18: 290-3)